Design and simulation of 20MHz oscillator using CMOS-MEMS beam resonators - Zainuddin, Ahmad Anwar (IEEE, 2013)
We present the design and analysis result of a low power, low noise, 20 MHz CMOS-MEMS oscillators. To perform oscillator circuit simulations, the CMOS-MEMS resonator (Clamped-Clamped beam) was modeled using its RLC equivalent circuits. For a MEMS resonator to be able to function as an oscillator it needs to be coupled with supporting amplifier circuits. The MEMS beam resonator has 73dB insertion loss which translates to motional resistance of Rx=3MΩ, capacitance, Cx=4.58aF and inductance, Lx=14.5H respectively. The amplifier design is based on the requirement for oscillation, which is, the loop gain of one and the zero phase shifts. For this work, the pierce circuit topology was chosen due to its simplicity and high frequency stability. Both the amplifier and beam resonators were designed using Silterra's CMOS technology. The design of the amplifier comprises of 6 transistors, which are integrated with the MEMS beam resonator to form an oscillator. The proposed CMOS-MEMS oscillators is capable of generating 20 MHz clocks. The beam resonators require approximately 40VDC and 400mV, VAC to vibrate. The actuation was simulated and measured using Finite modeling software, FEM and Cadence to obtain the desired design parameters. The design of 20MHz oscillator produces output power -1.45dBm by using 1.8V power supply.